Biomimicry approach adapted from the fundamentals of design development process / Azhari Md Hashim and Muhammad Faiq Hilmi Mohamad Zamberi - Md Hashim, Azharı; Mohamad Zamberi, Muhammad Faiq Hilmi (UiTM Cawangan Kedah, 2021)
Transport design inspiration form that requires the observation from the surrounding environment derived from the attribute and imitating inspiration between nature and transportation. The designer was inspired by the potential form obtained from the physically or philosophically aspect underneath nature's living organisms during the early phases of transport design development, particularly during the conceptual and proposal phases. As a result, researchers and designers began to aspire to nature as a problem solver in their conceptual design. This study aims to investigate natural characteristics that can be incorporated into transportation design projects through the design learning process, as well as obtaining an understanding of the users' perceptions of the suggested design. In this project, the learning process comprises of evaluating the design influence, system, and technology that emphasizes on the attributes of nature. As an outcome, a survey involving potential users was conducted by utilising questionnaires and distributed to the respondents. Finally, the findings demonstrated how nature may be used as a tool of research to break down barriers between natural science and engineering disciplines, notably in the domain of design. Furthermore, the responses revealed the respondents' views on the design as references in academic and industry practises.